Mortality in Pacus (Piaractusmesopotamicus) caused by Pantoeaagglomerans and Pseudomonas aeruginosa in Excavated Tank - Wolff Ferreira, Milena; Martins Santos, Ricardo; Rodrigues da Silva, Alanderson; Saory Makimoto, Sarah; Capibaribe Barbosa, Guilherme Ribeiro; Braziliano de Andrade, Gisele (Acta Scientiae Veterinariae, 2019)
Background:Fish production in Brazil is growing strongly. This growth is being mainly driven by mainland aquaculture, which in 2017 produced 691.700 tons of fish. Toimprove production levels, fish farms have become increasingly intensive, but in these systems, the high fish densities in the ponds, the high feeding rate, and the high organic matter levels in the water can lead the fish becoming stressed. This can cause bacterial proliferationand an increase in mortality. Most species of fish-causing bacteria are saprophytes. They are found naturally in the environment and are usually responsible for secondary or opportunistic infections.Thisstudy reports on an outbreak of Pacus (Piaractusmesopotamicus) mortality at an intensive fish farm, in the municipality of Campo Grande, MS, Brazil,that used excavated tanks. Cases:The outbreak occurred at a fish farm in the municipality of Campo Grande, MS, during August, 2015. A total of 200 pacus in two tanks died after they showedthe following symptoms: lethargy, anorexia, increased mucus production, and disordered swimming and water surface searching. The temperature and dissolved oxygen were measured using a digital thermometer and an oximeter, respectively, and water transparency was measured with a Secchi disc. The pH was measured usinga portable digital potentiometer. The values for the water quality parameters analyzed during the mortality period were temperature, 22.5oC; transparency, 20cm; oxygen dissolved in the early morning 3mg/L and at the end of the afternoon, 4.5mg/L; pH 8.3; and toxic ammonia, 0.002ppm. Five fishes were collected from the tank, immediately cooled to 4°C, and sent to the Microbiology and Pathology Laboratories to perform the microbiological and pathological laboratory procedures.After the replication process, the slow glucose fermentation characteristics in MacConkey Agarand other biochemical tests showed that the lactose non-fermenter bacterium was Pseudomonas aeruginosa and the fermenting bacterium was Pantoeaagglomerans. A necroscopic examination revealed congestion of viscera in general and thickening of the gills; the histopathological examination showed an intense inflammatory reaction in the gills; andthe liver showed congestion and dilation of the central, hepatoportal, and sinusoidal veins,marked cytoplasmic vacuolization, the presence of hemosiderin and leukocytosis, and coagulation necrosis and cholestasis foci. Discussion:The water temperature in the tanks (22.5°C) was lower than what is considered ideal for tropical fish. It ranged from 25 to 32°C. Furthermore,the pH (8.3) was close to the limit of what is considered appropriate. The mean tank flow rate at the time of death was 15 L/min, corresponding to a daily renewal rate of 1.2%, which was lower than the 10% per day recommended as the ideal ratefor excavated ponds in a semi-intensive production system. The decreased water flow in the tank during the period when mortality was recorded caused an increase in the amount of accumulated organic matter. This rise is commonly referred to as eutrophication, which is characterized by an increase in the rate of decomposition and release of nutrients into the water. The excess nutrients, mainly nitrogen and phosphorus, cause excessive phytoplankton and aquatic macrophyte growth, which results in a significant reduction in the amount of dissolved oxygen, particularly during periods of low photosynthetic activity.In this case study, the cause of the fish mortalitywas attributed to opportunistic infection by Pantoeaagglomeransand Pseudomonas aeruginosacaused by imbalances in water quality.